Disharmonisasi Penormaan Final dan Mengikat Antara Putusan Dewan Kehormatan Penyelenggara Pemilihan Umum Dengan Putusan Peradilan Tata Usaha Negara - Kurniawaty, Yuliana Rosalita; Ayuni, Qurrata (Universitas Sang Bumi Ruwa Jurai, 2025)
The aim of this research is to obtain an alternative solution to the disharmonizing of final and binding norms between the decision of the Honorary Council of General Election Organizers and the Decision of the State Administrative Court. This research uses a doctrinal approach by explaining and testing legal problems based on relevant previous legal doctrine or opinions. The research results show that there are problems in implementing the final and binding DKPP Decision which has been confirmed and tested through the Constitutional Court Decision Number: 31/PUU-XI/2013. Election organizers have a legal obligation to implement DKPP decisions because there are no other legal remedies when a case has been decided by DKPP. The definition of final and binding means forcing all election management institutions to carry it out in accordance with the original intent of establishing the DKPP. Therefore, in order to protect and maintain the DKPP's very strategic authority as an election organ, the DKPP should be given immunity rights, including for DKPP decisions which cannot be challenged in the judicial process. Apart from that, regulations are needed to provide limitations and scope of KTUN qualifications and/or types of KTUN exceptions that can be disputed in the TUN court